(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The works of scientists who studied the genre of poetry in linguistics are described. The language of poetry is analyzed, the stylistic features of poetry, positive and negative aspects are analyzed, and a conclusion is drawn. The main systematic structures of linguopoetics and their use in a work of art are listed.